Fingered Citron—A Fragrant Ornamental Fruit Crop for Florida - Yuheng Qiu; Mary Dixon; Jonathan Denison; Fernando Alferez; Guodong Liu (EDIS)
The purpose of this new 4-page publication of the UF/IFAS Horticultural Sciences Department is to introduce fingered citron to county Extension faculty, students interested in crop production, growers, certified crop advisors, crop consultants, consumers, environmentalists, and policy makers in the agricultural sector for better production, consumption, and environmental sustainability. Written by Yuheng Qiu, Mary Dixon, Jonathan Denison, Fernando Alferez, and Guodong Liu. https://edis.ifas.ufl.edu/hs1427